Dampak Kepuasan dan Kepercayaan terhadap Loyalitas Nasabah dalam Sistem M-Payment - Angellica Natalia Putri (CV. Strata Persada Academia, 2023)
This study aims to prove the impact of satisfaction and trust on consumer loyalty in m-payment payments which are currently in vogue. the test results with the help of SPSS prove that satisfaction has a positive impact on loyalty while trust does not have an impact on customer loyalty in using M-Payment services. This study used convenience sampling which turned out to be less able to generalize the results of the study. The results of this study indicate that satisfaction has an effect on loyalty and this research has succeeded in showing the other side of trust that has no impact on consumer loyalty. In addition, the test results also show that most of the respondents are young people, which means that the demographics of the respondents are also uneven. Therefore, further research is expected to pay attention to this matter.